PENURUNAN BERAT BADAN DENGAN LATIHAN PENCAK SILAT PADA PERGURUAN PSHT DESA SRI MULYO TERAWAS - Wawan Syafutra; Niko Fransega; Nova Rifai (LP4MK STKIP PGRI Lubuklinggau, 2022)
The purpose of this study is to determine whether there is the effect of weight loss by pencak silat training method using random sampling research design. The population in this study was a student of PSHT colleges, totaling 10 sampling techniques by means of total sampling and variables in this study, namely physical exercise. Data analysis using t-test statistics. The instrument used in this study was the instrument of testing the ball/weight measurement. The results of the initial test mean were 26.67 and the final test 19.88. From the difference results the difference was obtained for the experimental group of 7,723 T-count value of 15.081 with a table value of 0.171 with a significance of 0.00 ≥ 0.05. Then it can be concluded that the physical training method increases.